EFEKTIFITAS PEMBERIAN PROBIOTIK TERHADAP DURASI DIARE ANAK DI RUMAH SAKIT PKU MUHAMMADIYAH BANTUL YOGYAKARTA - Sri Mulyani; Dyah Aryani Perwitasari; Nurcholid Umam (Pharmaciana, 2016)
Diarrhea is the second leading cause of children’s death worldwide, including in Indonesia.With regard to reducing the number of death, it is highly needed to provide a quick and accurate treatment. In clinical practice, prebiotics has been widely used as a treatment, particularly in the case of acute diarrhea in children. However, it is still not recommended by WHO. This study is aimed to determine the treatment pattern of diarrhea in children’s ward at PKU Muhammadiyah Bantul Hospital and determine whether probiotic supplementation on standard therapy results a decrease in the duration of diarrhea which is better than only the standard therapy in the management of acute diarrhea in children. This study used retrospective cohort design using data from medical records with diagnose acute diarrhea or acute gastroenteritis (ICD A09). The data was collected from January to December 2014, at children’2 ward, PKU Muhammadiyah Bantul Hospital, Yogyakarta. Data was divided into three groups: (i) Group I those who were treated by using standard therapeutic with rehydration and zinc, (ii). Group II those who were treated by combination of rehydration, zinc and probiotics, (iii) Group III those who were treated with rehydration and probiotics. Data duration of diarrhea as an outcome of the effectiveness of probiotics analyzed statistically to determine differences in outcomes between groups. Among the three groups, Group I, Group II and group III gained an average duration of diarrhea 66.33 (SD 21.66) hours, 55.32 (SD 19.07) hours and 54.79 (SD 17.69) hours, respectively. The statistical test shows that there is significant different from diarrhea duration among the three groups (p = 0.014). The test results between probiotic groups (II and III) and the control group is significantly different with p-value 0.018 and 0.011, respectively. While the group II and group III do not differ significantly (p = 0.898). Treatment pattern therapy of diarrhea in PKU Muhammadiyah Bantul Hospital divided into three kinds of therapy. The first is rehydration therapy and zinc supplementation, the second is rehydration therapy and zinc supplementation and probiotics, the third is rehydration therapy and probiotics. Probiotic supplementation is proven effective in reducing the duration of diarrhea significantly compared to patients who were received standard therapy.